Honokiol Inhibits HIF-1α-Mediated Glycolysis to Halt Breast Cancer Growth - Yi, Xianglan; Qi, Mengxin; Huang, Mingxiang; Zhou, Sheng; Xiong, Jing (Frontiers in Pharmacology, 2022)
Background: Hypoxia-inducible factor-1α (HIF-1α) induces the expression of glycolysis-related genes, which plays a direct and key role in Warburg effect. In a recent study, honokiol (HNK) was identified as one of the potential agents that inhibited the HIF-1α signaling pathway. Because the HIF- 1α pathway is closely associated with glycolysis, we investigated whether HNK inhibited HIF-1α-mediated glycolysis. Methods: The effects of HNK on HIF-1α-mediated glycolysis and other glycolysis-related genes’ expressions, cancer cells apoptosis and tumor growth were studied in various human breast cancer models in vitro and in vivo. We performed the following tests: extracellular acidification and oxygen consumption rate assays, glucose uptake, lactate, and ATP assays for testing glycolysis; WST-1 assay for investigating cell viability; colony formation assay for determining clonogenicity; flow cytometry for assessing cell apoptosis; qPCR and Western blot for determining the expression of HIF-1α, GLUT1, HK2 and PDK1. The mechanisms of which HNK functions as a direct inhibitor of HIF-1α were verified through the ubiquitination assay, the Co-IP assay, and the cycloheximide (CHX) pulse-chase assay. Results: HNK increased the oxygen consumption rate while decreased the extracellular acidification rate in breast cancer cells; it further reduced glucose uptake, lactic acid production and ATP production in cancer cells. The inhibitory effect of HNK on glycolysis is HIF-1α-dependent. HNK also downregulated the expression of HIF-1α and its downstream regulators, including GLUT1, HK2 and PDK1. A mechanistic study demonstrated that HNK enhanced the self-ubiquitination of HIF-1α by recruiting two E3 ubiquitin ligases (UFL1 and BRE1B). In vitro, HNK inhibited cell proliferation and clonogenicity, as well as induced apoptosis of cancer cells. These effects were also HIF1a-dependent. In vivo, HNK inhibited tumor growth and HIF-1α-mediated glycolysis. Conclusion: HNK has an inhibitory effect on HIF-1α-mediated glycolysis in human breast cancer. Our research revealed a new mechanism of HNK as an anti-cancer drug, thus representing a novel strategy to improve the prognosis of cancer.